2012
DOI: 10.1245/s10434-012-2269-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Repeat Hepatic Resection in Patients with Recurrent Hepatocellular Carcinoma and Analysis of Recurrent Types and Their Prognosis: A Single-Center Experience in China

Abstract: Repeat hepatic resection resulted in much higher survival rates in the MO patients than in the IM patients. Repeat hepatic resection could be recommended for those patients in whom the recurrent HCC occurs more than 18 months after initial resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
112
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(126 citation statements)
references
References 34 publications
11
112
2
Order By: Relevance
“…For recurrent HCCs, MO patients have been shown to have a better outcome than IM patients (Yasui et al, 1997;Huang et al, 2012). Additionally, a recurrence-free time of more than 18 months after the initial hepatic resection has been suggested as a cutoff point to differentiate MO from IM in clinical practice (Huang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For recurrent HCCs, MO patients have been shown to have a better outcome than IM patients (Yasui et al, 1997;Huang et al, 2012). Additionally, a recurrence-free time of more than 18 months after the initial hepatic resection has been suggested as a cutoff point to differentiate MO from IM in clinical practice (Huang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recurrence-free time of more than 18 months after the initial hepatic resection has been suggested as a cutoff point to differentiate MO from IM in clinical practice (Huang et al, 2012). However, in another study, a time of 2 years was suggested (Portolani et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5-year cumulative recurrence rates are 77%-100%, and 80%-95% of recurrences are confined to the remnant liver (Huang et al, 2012). Effective therapeutic strategies for intrahepatic recurrence are critical in prolonging survival after liver resection.…”
Section: Recurrent Hepatocellular Carcinomamentioning
confidence: 99%
“…The 5-year survival rate after repeat liver resection varies from 23% to 69% in different studies, suggesting that repeat liver resection results in good outcomes in selected patients (Huang et al, 2012). However, the selection criteria of repeat liver resection for recurrent HCC remain vague and controversial.…”
Section: Recurrent Hepatocellular Carcinomamentioning
confidence: 99%